Pemanfaatan Persamaan Diferensial dalam Desain Filter Elektronik - Yannuansa, Nanndo (Elconika: Jurnal Teknik Elektro, 2024)
Differential equations play a crucial role in the analysis and design of electronic filters used in various applications, such as communication, signal processing, and control systems. This research aims to explore the application of differential equations in designing electronic filters, particularly in determining frequency response and system stability. The methods employed in this research include mathematical modeling of filters using first and second-order differential equations, as well as numerical simulations to evaluate filter performance. The results of the study demonstrate that the application of differential equations enables the design of filters with optimal frequency characteristics, whether in low-pass, high-pass, band-pass, or band-stop filters. The conclusion of this research affirms that differential equations are an effective tool in optimizing the design of electronic filters for various industrial and academic needs